Cruzipain and Its Physiological Inhibitor, Chagasin, as a DNA-Based Therapeutic Vaccine Against Trypanosoma cruzi - Cerny, Natacha; Bivona, Augusto Ernesto; Sanchez Alberti, Andrés; Trinitario, Sebastián Nicolás; Morales, Celina; Cardoso Landaburu, Alejandro; Cazorla, Silvia Inés; Malchiodi, Emilio Luis (Frontiers in Immunology, 2020)
Chagas disease caused by the protozoan parasite Trypanosoma cruzi is endemic in 21 Latin America countries and the southern United States of America, and now is spreading into several other countries due to migration. Despite the efforts to control the vector throughout the Americas, currently there are almost 7 million infected people worldwide, causing approximately 10,000 deaths per year, and 70 million people at risk to acquire the infection. Chagas disease treatment is restricted only to two parasiticidal drugs, benznidazole and nifurtimox which are effective during the acute and early infections but have not been found to be as effective in chronic infection. No prophylactic or therapeutic vaccine for human use has been communicated at this moment. Here we evaluate in a mouse model, a therapeutic DNA vaccine combining Cruzipain (Cz), a T. cruzi cysteine protease that proved to be protective in several settings, and Chagasin (Chg), which is the natural Cz inhibitor. The DNA of both antigens, as well as a plasmid encoding GM-CSF as adjuvant, were orally administrated and delivered by an attenuated Salmonella strain to treat mice during the acute phase of T. cruzi infection. The bi-component vaccine based on Salmonella carrying Cz and Chg (SChg+SCz) was able to improve the protection obtained by each antigen as mono-component therapeutic vaccine and significantly increased the titers of antigen- and parasite-specific antibodies. More importantly, the bicomponent vaccine triggered a robust cellular response with IFN-γ secretion that rapidly reduced the parasitemia during the acute phase and decreased the tissue damage in the chronic stage of the infection, suggesting it could be an effective tool to ameliorate the pathology associated to Chagas disease.